AN ANALYSIS OF SPEECH ACTS PERFORMED IN THE UNITED STATES OF BARRACK OBAMA'S SPEECH ELECTION 2009 - Fitria Herliana Rahmayani; Risa Dwiyuliana (PROJECT (Professional Journal of English Education), 2018)
This study deals with the Speech Acts. The aim of this study is one type of speech to be analyzed using speech actsand to find out the frequency of each speech acts in the United States video’s speech entitled Barrack Obama’s. This study was conducted by using descriptive qualitative research. The data was be accepted from video script of Barrack Obama’s Speech. Documentary technique is used in collecting data. The findings showed that there are five types of words that will be found in the Barack Obama’s speech video script and there are representative, directive, declarative, expressive, and commisive. The initial type of speech acts is representative ( 34 words ), the second is directive ( 12 words ), the third isdeclarative ( 5 words ), the fourth expressive ( 4 words ), and the last is commisive ( 4 words ).